Variation in hierarchical guild structure between two bird assemblages of a wetland in the Mexican Pacific - Ruiz Bruce Taylor, Mateo Donald; Rangel Salazar, José Luis; Enríquez, Paula; León-Cortés, Jorge L.; García-Estrada, Carlos (Revista de Biología Tropical, 2017)
Neotropical wetlands comprise contrasting habitats with highly diverse avifauna, including herbivores, insectivores and carnivores, of both terrestrial and aquatic species. Therefore, comparisons between wetland bird assemblages based only on species identity may disregard turnover within ecological groups, and eclipse important variations between habitat types. We studied bird assemblages from mangrove and estuary habitat types from a coastal lagoon system in Oaxaca, Mexico. For this, we used 640 point counts to obtain data on bird species using those habitats between October 2009 and May 2012. We ascertained guild structure by classifying 139 species in a scalar hierarchy of two-levels: 17 key-resource guilds nested within seven trophic guilds. To evaluate variation in guild structure between habitat types, we contrasted richness and diversity across trophic guilds and tested for variation in abundance within key-resource guilds. We exposed a tendency of greater diversity within terrestrial guilds in mangrove and within aquatic guilds at the estuary. However, these differences were compensatory and neither richness nor diversity varied between habitat types in comparisons across the sets of trophic guilds. Parallel analyses at two hierarchical levels supported the theoretical prediction of greater change at lower levels. Herpetofauna, wood invertebrates, aquatic invertebrates and seeds emerged as dietary components that may explain the distribution of abundance in key-resource guilds. Although the guilds from mangrove and estuary produced comparable sets of richness and diversity values, the actual identity of guilds with high values varied between habitats. On the other hand, species abundance comparisons within guilds pinpointed specific associations with habitat types and this method represents a suitable strategy for identifying habitat preferences in complex wetland bird assemblages.